2009
DOI: 10.1097/aln.0b013e31819fae06
|View full text |Cite
|
Sign up to set email alerts
|

Does a Higher Positive End Expiratory Pressure Decrease Mortality in Acute Respiratory Distress Syndrome?

Abstract: High PEEP strategy may have a clinically relevant independent mortality benefit. Despite a possible increase in baro-trauma, the benefits far outweigh potential risks. Current evidence therefore favors the use of high PEEP as the preferred option when ventilating patients with severe acute respiratory distress syndrome. As the reduction in absolute risk of death is less than 5%, a future clinical trial aimed at demonstrating statistical significance is likely to pose considerable financial and ethical burdens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 22 publications
0
53
0
9
Order By: Relevance
“…Our study differs from prior meta-analyses 19,20,33 in several ways. First, our study includes the most recently published randomized controlled trial.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Our study differs from prior meta-analyses 19,20,33 in several ways. First, our study includes the most recently published randomized controlled trial.…”
Section: Discussionmentioning
confidence: 62%
“…Third, we performed a sensitivity analysis with adjusted data from the 2 studies in which those data were available. 15,16 In contrast, 2 prior meta-analyses 19,20 pooled adjusted hospital mortality from one study 15 (where adjusted mortality favored higher PEEP), but did not include adjusted data from another trial that had imbalances in baseline characteristics 16 (adjusted data less favorable to higher PEEP). These 2 meta-analyses consequently reported an effect of higher PEEP on hospital mortality as a pooled odds ratio of 0.86 (95% CI 0.72-1.02) 20 and a pooled RR of 0.90 (95% CI 0.81-1.01).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Even with arbitrary setting of high or low PEEP, a recent metaanalysis suggested a 4% mortality benefit from high PEEP alone with ARDS patients. 5 Smaller studies have set PEEP according to lung mechanics and found improved and sustained oxygenation, but the studies were not large enough to identify an improvement in clinical outcomes. [6][7][8] In a recent randomized controlled trial, patients were allocated to receive mechanical ventilation either according to the ARDS Network protocol or guided by pleural pressure measured with esophageal balloon manometry.…”
Section: Introductionmentioning
confidence: 99%